You can never be too rich : - Haft, Alan (Wiley, 2008)
Every day, nationally recognized financial advisor Alan Haft helps his clients reach their financial goals and increase their standard of living. Now, in You Can Never Be Too Rich, Haft uses his vast knowledge base, highly innovative investment concepts, and entertaining style of writing to create proven investment solutions that will help readers minimize risk and take advantage of opportunities that lead to financial security for a lifetime. With this essential guide, Haft walks readers through the process of building and protecting wealth-and reveals the financial secrets that most investment professionals aren't aware of. You Can Never Be Too Rich clearly focuses on how people-whether they're just starting to work or are well on their way to retirement-can build a sizeable nest egg without getting caught up in market swings, taxes, or poor investment decisions. In this book, Haft doesn't rely on gimmicks or get-rich-quick schemes to help readers reach their goals; he simply offers proven and easy-to-understand-yet highly effective-advice that will allow them to make profitable financial decisions based on their specific situations.